Manajemen Pengembangan Bakat dan Minat Peserta Didik di Madrasah Aliyah Negeri 1 Tidore - Mubin Noho; Kamarun M. Sebe; Andy Andy; Minggusta Juliadarma; Sofyan Rumalean; Nadi Osamalu (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2022)
The research aims to elaborate on the management of talent and interest development in students at Islamic High School (Madrasah Aliyah Negeri, MAN) 1 Tidore and identify the supporting and inhibiting factors in the management of developing interests and talents in students at MAN 1 Tidore. The results showed that talent and interest development management was managed by the deputy head of student affairs, extracurricular coaches, student organization coaches, and students council (OSIS). Management stages include planning, implementation, and evaluation stages. This research contributes to the management studies on developing students' talents and interests in Islamic schools integrated into the school system and elaborates on the supporting and inhibiting factors. The supporting factors for the implementation of the management of the development of student's talents and interests include the solid cooperation and performance of all madrasah parties, the effective and efficient use of funds through BOS funds, adequate facilities and infrastructure, and the figure factor of the principal of MAN 1 Tidore. The inhibiting factors include spreading Covid-19 and natural/weather factors, irregular (routine) extracurricular activities, and the absence of counselor teachers.